Taxonomic placement of Onuris hauthalii (Brassicaceae: Eudemeae), based on morphology and multilocus species tree analyses, and the recognition of the new genus Alshehbazia - Salariato, Diego Leonel (2015)
Onuris hauthalii is a species distributed in Southern Argentina and Chile. Its generic assignment has been controversial, being included in Eudema, Brayopsis and Onuris. In order to clarify its generic affinities, we studied its morphology and phylogenetic relationships using multilocus/multispecies coalescent species-tree analyses based on four DNA regions (ITS, trnL-F, trnH-psbA, and rps16 intron). Results show that while O. hauthalii is related to Onuris s.s., it represents a well-differentiated lineage characterised primarily by having branched rhizomes, rosette flowering with ebracteate flowers, and latiseptate silicles. Based on the morphological and molecular evidence, we place this species in the new monospecific genus Alshehbazia. A description, morphological key, updated geographical distributions, map, and illustration are provided.